17‐3: A Novel Pixel‐level Local Dimming Backlight System for HDR Display Based on mini‐LED. Issue 1 (25th September 2020) - Guan, Enhui; Cheng, Xinyi; Zhang, Xiao; Wang, Zhimao; Xitong, Ma; Duan, Ran; Xianzhen, Li; Liang, Li; Chen, Shuo; Xinxin, Mu
Abstract : Recently, people present higher standard of the luminance and contrast for display system, especially for large UHD display which increasingly demands for HDR 1000 compatible. Compared with the side‐emitting LED backlight, direct lit‐type backlight can provides higher luminance, but global backlight control cannot satisfy high requirement for the contrast and the power loss. In order to improve the performance the backlight system, the local dimming backlight control with Mini‐LED become one of the best choices for us. In this paper, we present a pixel‐level local dimming backlight system, which is applied for the 75 inch UHD display system.